PENGARUH PENDAPATAN TERHADAP MARGINAL PROPENSITY TO SAVE (MPS) RUMAH TANGGA PADA PEGAWAI NEGERI SIPIL (PNS) DI IAIN BONE - Musrini Muis (Fakultas Ekonomi dan Bisnis Islam IAIN Bone, 2021)
This study discusses the Effect of Income towards household Marginal Prospenstiy to Save (MPS) on Civil Servants (PNS) at IAIN Bone. The objectives of this study are: (1) To determine the effect of income on household marginal propensity to save (MPS) in civil servants at IAIN Bone (2) to determinehousehold marginal propensity to save (MPS) in civil servants at IAIN Bone.This study uses quantitative research with an Islamic microeconomic approach with a total sample of 61 respondents. The data collection method used is questionnaire method (questionnaire) and documentation method. The data analysis technique used is descriptive analysis and simple linear regression analysis with the tests used in the form of validity and reliability to determine the effect of income variables on the Marginal Propensity to Save (MPS) variable, which previously tested normality and linearity. Subsequently, hypothesis testing is done in the form of simultaneous tests (f test) and Partial Test (T Test). The results of these studies, viewed linearly that the Income variable has a linear relationship to Marginal Propensity to Save (MPS) about 0.383.Based on Marginal Propensity tosave from 61 respondents surveyed, there were 20 people or 33% of respondents who had a higher Marginal Propensity toSave compared to their Consumption Expenditures. While 41 people or 67% of respondents have higher consumption expenditure compared to Marginal Propensity To Save.